Brain-computer interfaces and human factors: the role of language and cultural differences—Still a missing gap? - Herbert, Cornelia (Frontiers in Human Neuroscience, 2024)
Brain-computer interfaces (BCIs) aim at the non-invasive investigation of brain activity for supporting communication and interaction of the users with their environment by means of brain-machine assisted technologies. Despite continuous technological progress in the field and promising research aimed at understanding the role of human factors in supporting BCI efficiency, a few topics still remain uncharted. The aim of this paper is to discuss why it is important to take the language of the user, its embodied grounding in perception, action and emotions, and its interaction with cultural differences in information processing of the user into consideration in future BCI research. Based on evidence from recent studies, it is proposed that detection of residual language abilities and language training are two main objectives and key topics of enquiry of future BCI studies to improve communication especially among vulnerable BCI users from bench to bedside and real world applications. In addition, cultural differences shape perception, actions, cognition, language and emotions subjectively, behaviorally as well as neuronally. Therefore, BCI applications should consider cultural differences in information processing to develop culture- and language-sensitive BCI applications for different user groups and BCIs, and investigate the linguistic and cultural contexts in which the BCI will be used.